2019
DOI: 10.1038/s41467-019-09730-9
|View full text |Cite
|
Sign up to set email alerts
|

Colossal barocaloric effects near room temperature in plastic crystals of neopentylglycol

Abstract: There is currently great interest in replacing the harmful volatile hydrofluorocarbon fluids used in refrigeration and air-conditioning with solid materials that display magnetocaloric, electrocaloric or mechanocaloric effects. However, the field-driven thermal changes in all of these caloric materials fall short with respect to their fluid counterparts. Here we show that plastic crystals of neopentylglycol (CH 3 ) 2 C(CH 2 OH) 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(215 citation statements)
references
References 59 publications
6
202
3
4
Order By: Relevance
“…The barocaloric effect is defined as the temperature change induced by a change in pressure under the adiabatic condition, or by the entropy change per unit of pressure change under the isothermal condition . It is shown that the barocaloric strength of MDABCO is superior to oxide perovskite ferroelectrics such as BaTiO 3 and PbTiO 3 , but inferior to recently studied plastic crystals . One possible reason is the intermediate hardness of MDABCO between the softer plastic crystals and the harder oxide perovskite ferroelectrics.…”
mentioning
confidence: 99%
“…The barocaloric effect is defined as the temperature change induced by a change in pressure under the adiabatic condition, or by the entropy change per unit of pressure change under the isothermal condition . It is shown that the barocaloric strength of MDABCO is superior to oxide perovskite ferroelectrics such as BaTiO 3 and PbTiO 3 , but inferior to recently studied plastic crystals . One possible reason is the intermediate hardness of MDABCO between the softer plastic crystals and the harder oxide perovskite ferroelectrics.…”
mentioning
confidence: 99%
“…In Table 3, we enclose some of the most representative BC compounds along with some basic refrigerant characteristics. To date, giant BC effects have been measured in a number of organic-inorganic hybrid perovskites [99,100], shape-memory alloys [115][116][117], polar compounds [118,119], the archetypal fast-ion conductor AgI [120], fluoride-based materials [121], polymers [122], and molecular crystals [123][124][125][126]. The phase transitions leading to the giant BC effects reported in Table 3 present some similarities to those explained in preceding sections, made the exception of molecular crystals.…”
Section: Overview Of Barocaloric Performancesmentioning
confidence: 99%
“…The barocaloric strengths and giant adiabatic temperature changes measured in molecular crystals, reported within the last few years, are very impressive. For instance, the |ΔT(qd)| obtained in neopentylglycol, with chemical formula (CH3)2C(CH2OH)2 [1,123,124], amounts to 45-50 K near room temperature, which actually deserves the adjective "colossal". On the other hand, the ΔT/ΔP values reported in the magnetic compounds [Fe(pzt)6](PF6)2 [125] and [FeL2][BF4]2 [126] are superior to those achieved in the rest materials listed in Table 3, made the exception of the hybrid perovskites [TPrA][Mn(dca)3] (although their corresponding operating temperatures probably are too low).…”
Section: Recent Developmentsmentioning
confidence: 99%
See 2 more Smart Citations